A Clinical Update and Global Economic Burden of Rheumatoid Arthritis - Fazal, Syed A.; Khan, Mohammad; Nishi, Shamima E.; Alam, Fahmida; Zarin, Nowshin; Bari, Mohammad T.; Ashraf, Ghulam Md. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background and Objective: Rheumatoid arthritis (RA) is a predominant inflammatory autoimmune disorder. The incidence and prevalence of RA is increasing with considerable morbidity and mortality worldwide. The pathophysiology of RA has become clearer due to many significant research outputs during the last two decades. Many inflammatory cytokines involved in RA pathophysiology and the presence of autoantibodies are being used as potential biomarkers via the use of effective diagnostic techniques for the early diagnosis of RA. Currently, several disease-modifying anti-rheumatic drugs are being prescribed targeting RA pathophysiology, which have shown significant contributions in improving the disease outcomes. Discussion: Even though innovations in treatment strategies and monitoring are helping the patients to achieve early and sustained clinical and radiographic remission, the high cost of drugs and limited health care budgets are restricting the easy access of RA treatment. Both direct and indirect high cost of treatment are creating economic burden for the patients and affecting their quality of life. Conclusion: The aim of this review is to describe the updated concept of RA pathophysiology and highlight current diagnostic tools used for the early detection as well as prognosis - targeting several biomarkers of RA. Additionally, we explored the updated treatment options with side effects besides discussing the global economic burden.
Keywords: autoimmune disease